2021
DOI: 10.1016/j.marenvres.2021.105277
|View full text |Cite
|
Sign up to set email alerts
|

Sustained productivity and respiration of degrading kelp detritus in the shallow benthos: Detached or broken, but not dead

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 73 publications
4
24
0
Order By: Relevance
“…Detached macroalgal biomass, which has been exported and deposited subtidally, cannot necessarily be treated as detritus because it has been found to be actively respiring and growing without degrading or contributing carbon to the underlying sediments (Frontier et al. 2021). In these experiments, the amount of mass lost from the detritus deposited over time, or the change in concentration or amount of carbon mass in the underlying sediment or pore water (Barreiro et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detached macroalgal biomass, which has been exported and deposited subtidally, cannot necessarily be treated as detritus because it has been found to be actively respiring and growing without degrading or contributing carbon to the underlying sediments (Frontier et al. 2021). In these experiments, the amount of mass lost from the detritus deposited over time, or the change in concentration or amount of carbon mass in the underlying sediment or pore water (Barreiro et al.…”
Section: Resultsmentioning
confidence: 99%
“…These types of experiments are conducted mostly on sandy shore ecosystems, but similar degradation experiments have been conducted in benthic subtidal habitats (de Bettignies et al 2020, estuarine sandflats (Gladstone-Gallagher et al 2016), and in specific seabed hollows where algal blades are known to accumulate (Norkko et al 2004). Detached macroalgal biomass, which has been exported and deposited subtidally, cannot necessarily be treated as detritus because it has been found to be actively respiring and growing without degrading or contributing carbon to the underlying sediments (Frontier et al 2021). In these experiments, the amount of mass lost from the detritus deposited over time, or the change in concentration or amount of carbon mass in the underlying sediment or pore water (Barreiro et al 2013) serves as a measure of carbon transferred through abiotic decay or detritivore activity.…”
Section: Must Be In Englishmentioning
confidence: 99%
“…Warm temperate kelp has a 42%–45% lower total photosynthetic pigment concentration than cold temperate kelps (Wright & Foggo, 2021), suggesting it has lower photosynthetic capacity which is in line with the 48%–50% lower photosynthetic activity reported here. Although Frontier, de Bettignies, et al (2021) found no difference in net and gross primary production and photosynthetic efficiency (chlorophyll fluorescence) between in vitro L. hyperborea and L. ochroleuca , a subsequent field experiment by the same authors suggests declining photosynthetic efficiency with detrital age in L. ochroleuca and no change in L. hyperborea (Frontier, Mulas, et al, 2021). This case supports our findings and highlights that in situ experimental validation is essential.…”
Section: Discussionmentioning
confidence: 98%
“…Degradation of kelp POM may take several weeks or even months (de Bettignies et al, 2020b;Smale et al, 2022), with the photosynthetic capacity still partially intact (Frontier et al, 2021). This impacts on the potential for large-scale and longterm transport, and for how long the POM is left on the sea floor has bearing on the degradation rates and the associated bacterial community (Brunet et al, 2021).…”
Section: Sinking Speeds and Transportmentioning
confidence: 99%
“…Macroalgal tissue may be transported distances at the order of 1000 km and to depths of several thousands of meters (Harrold et al, 1998;Ortega et al, 2019). Simulation studies and in situ observations have also shown that POM from natural kelp populations can be transported beyond the natural habitats, both horizontally and vertically (Filbee-Dexter et al, 2018, 2020, and that it may degrade over time periods of months (Frontier et al, 2021;Smale et al, 2022). Despite this, it is yet unclear how exported biomass of kelp detritus is dispersed (Pedersen et al, 2021), how far it is transported, and how the matter is distributed between the near and far field.…”
Section: Introductionmentioning
confidence: 99%